Communication in the Noble Qur’an and the Prophetic Sunnah - Sikumbang, Rahima; Taufiq, Muhammad (MSJ : Majority Science Journal, 2025)
Communication science from the perspective of Al-Qur'anul Karim and Assunnah Annabawiyyah is very important to study because in the current era, especially in Indonesia, there are many groups that are most correct, most in accordance with religion. So in discussions, we often prioritize ego and even excessive fanaticism without considering the contribution of the Al-Qur'an and hadith in communicating. Therefore, the author describes this discussion into several sections which aim to make it easier for readers to understand how to communicate with other people and see the role of Al-Quran'ul Karim Assunnah Annabawiyah's perspective. By using the library research method or library study. The result is to know the appropriate way to communicate without avoiding conflict, division between people, maintaining peace and maintaining friendship. As well as maintaining the continuity of neighbourhood, society, nation and state because humans themselves are social creatures who need each other.